Monitoring and assesment of children’s gross motor development using cctv media - Arnis, Putri Yolanda; Mahyuddin, Nenny; Yaswinda; Suryana, Dadan (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background: Assessment of gross motor development in early childhood is a crucial component in monitoring children’s growth and readiness for daily physical activities. Accurate and ethical assessment methods are required to ensure that observations truly reflect children’s natural movements and behavior. Objective: This study aims to develop and implement a Closed Circuit Television (CCTV)-based monitoring method as a supporting medium for assessing children’s gross motor development. Method: This research employed a qualitative case study approach. The participants consisted of ten children, including six children aged 6–12 months and four children aged 12–24 months. Data were collected through direct observation, CCTV recordings, and interviews with related stakeholders. The CCTV system was used to continuously record children’s spontaneous movements during daily activities without interrupting their interaction or play. Result: The findings showed that the use of CCTV facilitated educators in conducting more objective, accurate, and repeatable assessments of gross motor development without directly disrupting children’s activities. Based on the assessment results, six children aged 6–12 months were categorized as fairly capable to capable, while four children aged 12–24 months were categorized as capable to very capable. The CCTV-based method produced more stable, objective, and well-documented observation data, thereby simplifying the assessment process. Conclusion: The use of CCTV technology enhances objectivity and ethical awareness in assessing early childhood gross motor development. This method enables assessments to be conducted without intruding on children’s natural activities, while ensuring data accuracy and continuity. The findings provide implications for further research, highlighting the potential of CCTV as an effective medium for evaluating motor development in early childhood settings.